Ordinance No. 32, §10: An Ordinance to Define Misdemeanors and Provide Penalty Therefor, and for Other Purposes, The Daily Morning Alaskan, Jun. 18, 1903, at 2 - (:unkn) unknown (My University, 1903)
Prohibited concealed carry of any weapon. Violators guilty of a misdemeanor, punishable by fine of not more than fifty dollars, or imprisonment in jail of not more than thirty days, or both.
Keywords: CARRY - CONCEALED